Seasonal Variation of Food Web Structure and Stability of a Typical Artificial Reef Ecosystem in Bohai Sea, China - Li, Shengpeng; Wang, Ruyue; Jiang, Yueming; Li, Yanyu; Zhu, Lin; Feng, Jianfeng (Frontiers in Marine Science, 2022)
The last thirty years have witnessed the degradation and loss of function in the ecosystem of Bohai Sea, China. Great efforts, such as artificial reefs, have been used to restore the ecosystem of Bohai Sea in recent years. Here, we examined seasonal variation of food webs in Juehua Island’s artificial reefs by Ecopath model. Results showed that the number of species, range of trophic level, energy cycle proportion, energy complexity, nutrition transfer efficiency and ecosystem maturity have increased from summer to autumn. However, food web stabilities of artificial reefs have no obvious change from summer to autumn. Loop analysis revealed that the heaviest feedback loops are the interactions among benthos, zooplankton and phytoplankton, and the predator-prey negative interaction strength between zooplankton and phytoplankton dominated the stability of the artificial reef, whether in summer or autumn. Our analysis of the food web properties provides important information that should be considered in future restoration plan of the marine ecosystem.